The Emerging Necessity for an Efficient Redressal in the Case of the Diplomatic Personnel's Abuse of Privileges and Immunities (International Journal of Food and Nutritional Sciences, 2022)
Certain safeguards in form of privileges and immunities from civil and criminal actions are granted to diplomats to ensure smooth relations and intercourse between nations and to ensure the safety of diplomatic personnel who acts as a representative of the respective head of their states in a foreign land. Such privileges and immunities are driven by customary law and practices, international conventions, and diplomatic agreements. The Vienna Convention of 1961 had clear provisions regarding the initiation and termination of privileges and immunities concerning diplomatic agents. It recognized customary practices but there were an absence of deterrence against criminal acts